2011
DOI: 10.1364/ao.50.003128
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Bessel beams in modified axially symmetric graded index structures

Abstract: We explore a general type of stable Bessel beams in graded index media. The proposed axially symmetric medium is characterized by an "α" index profile. Explicit solutions for the radial envelope of the field E(r) are derived in terms of generalized Bessel functions. Emphasis is given on illustrating how far the conditions of the proposed modified structure permit only a Bessel function of the first kind to be uniquely retained in the solution. This paper considers both the optical and mathematical aspects. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that the on-axis beam profile can be shaped to an arbitrary distribution, while the central lobe still maintains the invariant lateral profile within a limited region as in the case of the classical quasi-Bessel beam. However, as it does not necessarily maintain its side lobe profile invariant along the beam propagation, the newly generated beam falls into a category called the generalized Bessel beam, which exists both theoretically and experimentally [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the on-axis beam profile can be shaped to an arbitrary distribution, while the central lobe still maintains the invariant lateral profile within a limited region as in the case of the classical quasi-Bessel beam. However, as it does not necessarily maintain its side lobe profile invariant along the beam propagation, the newly generated beam falls into a category called the generalized Bessel beam, which exists both theoretically and experimentally [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%